Distance Education in the Period of Coronavirus Pandemics - Flera Ya. KHABIBULLINA; Iraida G. IVANOVA; Nikolaj A. KIRILLOV; Nadezhda V. SMIRNOVA (Communications of International Proceedings, 2021)
The article presents the results of a study on the attitude of participants in the educational process to the introduction of distance learning. Based on the analysis of the results obtained, the authors conclude that the transfer to a distance learning format during self-isolation was an effective and the only possible way to continue teaching students and schoolchildren during the coronovirus pandemic. At the same time, according to all participants of the educational process, including parents of students, distance education can not fully replace traditional education, as it leads to a decrease in the quality of education and deterioration of mental and somatic health indicators. With the further development of electronic methods of information transmission and telecommunications channels, the improvement of teaching methods and methods of prevention of mental and somatic diseases, distance learning is gradually becoming an obligatory attribute of the system of continuing education, which allows you to take advanced training courses and retraining of personnel on the basis of the best universities in the country and the world on the job.
Keywords: distance education; digital learning technologies; pandemic; mental and somatic health; electronic means of communication.